Classic Pro-Choice Thought Experiments and African Communitarianism - Lougheed, Kirk (Bioethics, 2025)
I analyse two classic pro-choice thought experiments in the Anglo-American philosophical literature in Thomson's Violinist Case and Tooley's Kitten Serum Case, in light of two prominent African normative theories. Though each of these cases is designed to generate pro-choice intuitions, I suggest they do not do so nearly as clearly when African normative theories are in view. Furthermore, even where they might yield a pro-choice verdict, they do so for very different reasons. That African ethics, which is often labelled communitarian, differs from what one typically finds in the Anglo-American normative tradition is hardly a new insight. However, that these differences might undermine the universality of pro-choice thought experiments about abortion in Anglo-American bioethics has yet to receive significant attention.